I am the messenger [Posol anglicky] - Zusak, Markus, 1975- (Alfred A. Knopf, 2010)
Ed Kennedy is an underage cabdriver without much of a future. He's pathetic at playing cards, hopelessly in love with his best friend, Audrey, and utterly devoted to his coffee-drinking dog, the Doorman. His life is one of peaceful routine and incompetence until he inadvertently stops a bank robbery.